تشکیل سماج کے تربیتی و عملی پہلو نبو ی سماجی تصورات کے تناظر میں: Educational and practical aspects of formation society in the context of prophetic social concepts - Farooq, Dr. Ghulam; Ahmad, Dr. Nisar Ahmad (Al-Amīr Research Journal for Islamic Studies, 2023)
Life is a process of uncovering the truth, knowing the laws of nature and building a supportive society consisting of intelligent people who develop a high moral consciousness based on the principles of morality based on the correct understanding of these laws. If a person is not clear in his goals, The highest institutions, despite having many facilities, are not able to act in a civilized manner in difficult situations. It is only a case in which man, due to knowledge and creativity endowed by nature, adapts to his circumstances. And has the ability to change the society. Problems are an integral part of every nation and society. When people prepare future plans to solve these problems on scientific and religious basis, the society gets better and better. And this is certain. Societies always learn from their history. Unless our society takes into account the reforming aspect of the society of the Prophet, peace and blessings of God be upon him, the reformation and training of the society cannot be done properly. Worship, ethics and political science or just a few principles and laws, but a comprehensive system provides life. Key Words: supportive society, civilized manner, peace and blessings, nature.